KEMAMPUAN MENULIS KALIMAT EFEKTIF SISWA KELAS XI SMA NEGERI 1 RAMBAH KABUPATEN ROKAN HULU - Yulvia, Fini Yulvia Fini; Burhanudin, Dudung Burhanudin Dudung; Razak, Abdul Razak Abdul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problem in this study show the ability of students to writes of effective sentence eleven grade students of SMA Negeri 1 Rambah Rokan Hulu regency. This study aims to determine the ability to write of affective sentence eleven grade students of SMA Negeri 1 Rambah Rokan Hulu regency. This research used quantitative descriptive method. Data collected by the technique of arranging test. The sample is 15% from each grade XI is that 37 students. The results showed that ability of students to writes of effective sentence eleven grade students of SMA Negeri 1 Rambah Rokan Hulu regency is sufficient. Can be seenfrom the 37 students as a source of research data there were 29 respondents were able to write effective sentences and 8 respondents are not able to. Based on observations of researchers, most mistakes made by students is an error equivalence, especially malfunctions sentence, in others students are able to.Key Words: ability writes of sentences, effective sentence.